Pengaruh Kepuasan Kerja, Motivasi Dan Disiplin Terhadap Kinerja Karyawan Outsourcing Pada Pt. Sindy Hutama Karya Kabupaten Paser - Ana Nor Andriana; M. Nor Rasyidi; Setio Utomo (Universitas Lambung Mangkurat, 2015)
The purpse of this research is to find out of the influence of job satisfaction, the motivation and disciplined against the performance of outsourcing employees on PT. Sindy Hutama Karya County of Paser. The Use samples with 100 people respondents. The research is a quantitative analysis of the descriptive statistics and SmartPls technique analysis. The result of reseach done that job satisfaction effect was 69%, the motivation 14% and disipline 19% influntial significantly againts the outsourcing of employee performance PT. Sindy Hutama Karya County of Paser.Keywords : Job Stisfaction, Motivation, Discipline and Employee Performance